Peningkatan Akses Pasar Digital bagi Pelaku Usaha Sektor Informal - Alamsyah, Alamsyah; Mahriani; Mahriani, Retna; Yusnaini, Yusnaini; Mulyana, Eka; Yanti, Mery (MITRA: Jurnal Pemberdayaan Masyarakat, 2024)
This community service aims to intervene the cognitive, effective, and psychomotor aspects of micro and small business actors in utilizing information and communication technology (ICT) as a tool to help their marketing, sales, and business transactions in e-commerce. The target group for service activities is 60 (sixty) villagers who live in three villages (Tanjung Dayang Selatan Village, Tanjung Dayang Utara Village, and Mandi Angin Village) in South Indralaya District, Ogan Ilir Regency, who are eligible and selected purposively. Transfer knowledge and skills using tutorial lectures, discussions, and practicum/simulation methods for two days at the Tanjung Dayang Selatan Village Hall. To maintain the continuity of activities, the service team collaborates with the Tanjung Dayang Selatan Village Youth Organization as a partner in implementing the service. Quantitatively, this project is evaluated by holding a pre-test and post-test which are analyzed using the t-test. Qualitatively, evaluation is carried out through observation and discussion with participants to identify weaknesses and obstacles faced by participants. The community service carried out over the past two days succeeded in increasing community knowledge about the digital market. The increasing of knowledge was statistically robust, t(59) = 29.4030, p < 0.05. Further assistance is needed so that this knowledge can trigger real practices among citizens in utilizing the digital market as a product marketing medium. The service team recommends to policy makers, both at the village and district level, to provide policy support and financial support for economic actors in the digital market.